Mitochondrial implications in bulbospinal muscular atrophy (Kennedy disease). Issue 1 (17th February 2016) - Finsterer, Josef; Mishra, Anushree; Wakil, Salma; Pennuto, Maria; Soraru, Gianni
Abstract: There is increasing evidence that mitochondrial functions are secondarily disturbed in bulbospinal muscular atrophy (BSMA). This review focuses on the relation between BSMA and the effect of the expanded polyglutamine (poly-Q) androgen receptor (AR) on mitochondrial functions. Mitochondrial functions in bulbospinal muscular atrophy (SBMA) are affected on the molecular, clinical, and therapeutic level. On the molecular level there is down-regulation of various nuclear-DNA-encoded mitochondrial proteins by mutant androgen receptor (mAR), colocalization of the mAR with various mitochondrial proteins, association of mAR aggregates with mitochondria resulting in abnormal distribution of mitochondria, mtDNA depletion or multiple mtDNA deletions, mitochondrial membrane depolarization, increase in reactive oxidative species, and activation of the mitochondrial caspase pathway. On the clinical level various mitochondrial disorders mimic SBMA, and on the therapeutic level pioglitazone expresses PPAR-γ, cyclosporine-A restores mitochondrial membrane potentials, coenzyme-Q and idebenone reduce oxidative stress, and geldanamycin up-regulates protective mitochondrial heat shock proteins. In conclusion, in BSMA mitochondrial dysfunction results from various interactions of elongated poly-Q AR with mitochondria, mitochondrial proteins, nuclear or mitochondrial DNA, causing oxidative stress, decreased mitochondrial membrane potential, or activation of the mitochondrial caspase pathway. Additionally, mitochondrial disease may mimic BSMA and therapeutic approaches may depend on modifications of mitochondrial pathways.